An Examination of De-Extinction: How Does De-Extinction Challenge Biodiversity Governance in International Environmental Law - Dipo Bijak Muhammad (Faculty of Law, Universitas Gadjah Mada, 2026)
Abstract The reported success of Colossal Biosciences in 2025 to achieve the first deextinction of Aenocyon dirus (dire wolf) has generated global fascination, yet it has largely been met with silence within the legal community. While scientists celebrate the achievement and the public marvels at its implications, international environmental law has not provided conceptual clarity on how such an unprecedented event should be situated. Whether driven by ecological responsibility or scientific curiosity, de-extinction raises profound questions that go beyond technical regulation. This paper argues that the issue must be approached through philosophical inquiry under international law, and international environmental law in particular is, at its core, a product of philosophical compromise. As such, this paper attempts to explore the motives of ecological responsibility underpinning de-extinction in relation to biodiversity. By tracing the doctrinal and philosophical underpinnings of legal obligations toward biodiversity, this article examines whether de-extinction represents a new shift toward an eco-centric paradigm or merely emphasizes existing anthropocentric frameworks. It ultimately argues that de-extinction reveals a conundrum: a biological and technologically produced organism without juridical recognition as components of biodiversity. Abstrak Keberhasilan Colossal Biosciences pada tahun 2025 dalam melakukan deeksistensi Aenocyon dirus (serigala purba) telah memunculkan perhatian global, tetapi justru banyak diabaikan oleh komunitas hukum. Sementara para ilmuwan merayakan pencapaian ini dan publik mengagumi implikasinya, hukum lingkungan internasional belum memberikan kejelasan konseptual mengenai bagaimana peristiwa yang belum pernah terjadi sebelumnya ini harus diposisikan. Terlepas dari apakah didorong oleh tanggung jawab ekologis atau rasa ingin tahu ilmiah, de-eksistensi menimbulkan pertanyaan mendalam yang melampaui aspek teknis regulasi. Artikel ini berargumen bahwa isu tersebut harus didekati melalui penyelidikan filosofis di bawah hukum internasional dan khususnya hukum lingkungan internasional, yang pada dasarnya dibentuk oleh landasan filosofis. Dikarenakan hal tersebut, artikel ini mencoba untuk menelusuri motif-motif dari tanggung jawab ekologis yang membawahi de-eksistensi dalam hubungannya terhadap keanekaragaman hayati. Dengan menelusuri landasan doktrinal dan filosofis dari kewajiban hukum terhadap keanekaragaman hayati, artikel inimenelaah apakah de-eksistensi merepresentasikan pergerakan baru menuju sebuah paradigma ekosentris atau sekadar menegaskan kerangka antroposentris yang ada. Artikel ini berargumen bahwa de-eksistensi mengungkap sebuah konundrum: keberadaan organisme biologis melalui teknologi tanpa pengakuanyuridis sebagai komponen keanekaragaman hayati.